stall Encodes an ADAMTS Metalloprotease and Interacts Genetically With Delta in Drosophila Ovarian Follicle Formation. - Ozdowski, E.F.; Mowery, Y.M.; Cronmiller, C. (Genetics, 2009)
Ovarian follicle formation in Drosophila melanogaster requires stall (stl) gene function, both within and outside the ovary, for follicle individualization, stalk cell intercalation, and oocyte localization. We have identified the stl transcript as CG3622 and confirmed the presence of three alternatively spliced isoforms, contrary to current genome annotation. Here we show that the gene is expressed in both ovarian and brain tissues, which is consistent with previous evidence of an ovary nonautonomous function. On the basis of amino acid sequence, stl encodes a metalloprotease similar to the "a disintegrin and metalloprotease with thrombospondin" (ADAMTS) family. Although stl mutant ovaries fail to maintain the branched structure of the fusome and periodically show improperly localized oocytes, stl mutants do not alter oocyte determination. Within the ovary, stl is expressed in pupal basal stalks and in adult somatic cells of the posterior germarium and the follicular poles. Genetically, stl exhibits a strong mutant interaction with Delta (Dl), and Dl mutant ovaries show altered stl expression patterns. Additionally, a previously described genetic interactor, daughterless, also modulates stl expression in the somatic ovary and may do so directly in its capacity as a basic helix-loop-helix (bHLH) transcription factor. We propose a complex model of long-range extraovarian signaling through secretion or extracellular domain shedding, together with local intraovarian protein modification, to explain the dual sites of Stl metalloprotease function in oogenesis.